2018
DOI: 10.1186/s40663-018-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting treeline dynamics in response to climate warming using forest stand maps and Landsat data in a temperate forest

Abstract: Background: Treeline dynamics have inevitable impacts on the forest treeline structure and composition. The present research sought to estimate treeline movement and structural shifts in response to recent warming in Cehennemdere, Turkey. After implementing an atmospheric correction, the geo-shifting of images was performed to match images together for a per pixel trend analysis. We developed a new approach based on the NDVI, LST (land surface temperature) data, air temperature data, and forest stand maps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
(142 reference statements)
1
8
0
Order By: Relevance
“…Maliheh Arekhi developed a new approach based on the NDVI, LST (land surface temperature) data, air temperature data, and forest stand maps over a 43-year period. The results show that during 1970-2013, the two pioneer tree species continued to expand and grow on open land, mainly in areas covered by rock and soil [36].…”
Section: Discussionmentioning
confidence: 97%
“…Maliheh Arekhi developed a new approach based on the NDVI, LST (land surface temperature) data, air temperature data, and forest stand maps over a 43-year period. The results show that during 1970-2013, the two pioneer tree species continued to expand and grow on open land, mainly in areas covered by rock and soil [36].…”
Section: Discussionmentioning
confidence: 97%
“…This alignment is reduced and eliminated by performing the geoshift code with "geoshift" function on images before the pixels were overlaid exactly for further comparison of the two data sets for all investigated variables (B1, B2, B3, B4, B5, NDVI, NDWI and EVI). To explain, performing geo shifting process completely omits the errors caused by the image to image misregistration and images' misalignment with a shift of 15 m to the west (x-direction) and 16 m to the north (y-direction) [45][46][47]. It is worth mentioning that Sentinel images were resampled to 30 meters and shifted to overlay the Landsat-8 OLI images, including B1, B2, B3, B4, B5, NDVI, NDWI and EVI, which are considered to be base images.…”
Section: Methods and Data Analysismentioning
confidence: 99%
“…This migration rate appears to be related to an estimated shift of the permafrost limit by +240 m during the last 50 years; they considered the climate warming a primary cause of the observed upward migration of high mountain plants. In a study of the treeline dynamics in response to climate warming in the Mediterranean region of Cehennemdere, Turkey, Arekhi et al (2018) found the geographical expansion of the treeline, with a migration rate of 20-40 m each decade, and the treeline altitude increased to 2,442 m from 2,335 m. In a study based on the supervised classification of historical (1953) and current (2015) aerial photographs on the spatial dynamics of the ecotone of alpine trees in the French Pyrenees, Feuillet et al (2020) observed an upward displacement of the tree line by ∼ 45 m on average, with at an overall rate of 0.73 m year −1 . Furthermore, during the study period, the minimum mean air temperatures increased by 0.6 • C, and the maximum mean air temperatures increased very slightly by 0.14 • C. Telwala et al (2013) surveyed historical (1849-1850) and the recent (2007)(2008)(2009)(2010) data on temperature and endemic species in elevational ranges at the alpine Sikkim Himalaya region and recorded a mean upward displacement rate of 27.53 ± 22.04 m per decade, which make to the montane floras, in particular, highly sensitive to climate change.…”
Section: Páramo Forest and Climate Changementioning
confidence: 99%